Changes in plant species richness in some riparian plant communities as a result of their colonisation by taxa of Reynoutria (Fallopia) - Tokarska-Guzik, Barbara; Bzdęga, Katarzyna; Knapik, Dagmara; Jenczała, Grzegorz (Biodiversity: Research and Conservation, 2006)
This study deals with the current issue of the synanthropisation of plant cover which manifests itself, amongst other ways, in the spreading of species outside the limits of their natural distribution range. The aim of the studies undertaken for the present report was to estimate the type and scale of threat posed by alien plant species to native plant diversity. The studies were carried out using the example of Reynoutria (Fallopia) species (knotweeds), which are considered to be invasive in our country as well as in other regions of the world. This is an attempt to determine the impact of these plants on the composition and diversity of the natural components of the herb layer in floodplain forest. Investigations were performed on permanent study plots localised in patches of floodplain forest which have been preserved in the valleys of the Soła, Biała and Jasienica rivers. The results of the field studies have confirmed the hypothesis that Reynoutria species exert a negative influence on the native components of the floodplain forest herb layer. This impact is, however, different with regard to the various life forms and ecological habitat groups of the plants. The increase of surface coverd by knotweeds does not significantly influence the development of early spring geophytes which are able to complete their full life cycle.